Studi Literature Pemahaman Bagi Hasil dan Kepercayaan Masyarakat dalam Keputusan Menabung di Bank Syariah - Sari, Nopita (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to analyze the relationship between public understanding of profit-sharing mechanisms and their level of trust in making saving decisions in Islamic banks. Using a literature review method, the research examines various scholarly sources such as journals, books, research reports, and regulations related to Islamic banking. The findings indicate that profit-sharing mechanisms, particularly the Mudharabah and Musharakah contracts, hold significant potential in attracting customers because they offer ethical alternatives aligned with Sharia principles. However, their effectiveness greatly depends on the level of Islamic financial literacy within society, as well as public perceptions of fairness, transparency, and risk management in their implementation. In addition, trust in Islamic banks built through service quality, oversight by the Sharia Supervisory Board, and public education plays a crucial role in influencing customer loyalty and saving decisions. The study also highlights several challenges, including low financial literacy, regulatory limitations, credit risk, and moral hazard, all of which can hinder the optimal application of the profit-sharing model. Overall, the findings emphasize the importance of enhancing Islamic financial literacy, strengthening governance, and promoting product innovation to build greater public trust and encourage wider participation in the Islamic financial system.